2024
DOI: 10.1002/ajmg.a.63565
|View full text |Cite
|
Sign up to set email alerts
|

Australian researcher's perspectives on the Australian industry‐led moratorium on genetic tests in life insurance

Tatiane Yanes,
Marisa Blencoe,
Antonia Howard
et al.

Abstract: Fear of insurance discrimination can inhibit genetic research participation. In 2019, an industry‐led partial moratorium on using genetic results in Australian life insurance underwriting was introduced. This mixed‐methods study used online surveys (n = 59 participants) and semi‐structured interviews (n = 22 participants) to capture researchers’ perceptions about the moratorium. 66% (n = 39/59) were aware of the moratorium before the survey. Of researchers returning genetic results, 56% (n = 22/39) reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…However, it is difficult to quantify the prevalence of GD due to methodological challenges such as ability to obtain data from insurance industry, thus, most research to date has relied on self-reported experiences. Nevertheless, fear of GD remains a deterrent to uptake of genetic testing in clinical and research settings [6][7][8][9][10][11][12][13][14] . With the emergence and increased use of new genetic technologies it is essential that we consider the unique challenges that may arise regarding GD.…”
mentioning
confidence: 99%
“…However, it is difficult to quantify the prevalence of GD due to methodological challenges such as ability to obtain data from insurance industry, thus, most research to date has relied on self-reported experiences. Nevertheless, fear of GD remains a deterrent to uptake of genetic testing in clinical and research settings [6][7][8][9][10][11][12][13][14] . With the emergence and increased use of new genetic technologies it is essential that we consider the unique challenges that may arise regarding GD.…”
mentioning
confidence: 99%